TANTANGAN DAN STRATEGI IMPLEMENTASI MP3EI KORIDOR KALIMANTAN - Kisno Hadi (Masyarakat Indonesia, 2012)
The development of Kalimantan corridor is one of key priorities in the economic masterplan (MP3EI). Kalimantan corridor plays a strategic function as a front line of Indonesias border with Malaysia and Brunei. For many years, Indonesia has neglected the development of this corridor. As a consequence, Kalimantan becomes an underdeveloped region. There is urgent need for restoring the infrastructure and transportation facilities, which are badly damaged and have been constraining access to the corridor. This paper has three main focuses: (i) the challenges of implementation of MP3EI; (ii) the need to recognize and adopt the innovation of local policies; and (iii) the implementation strategy for developing Kalimantan corridor.Keywords: Pembangunan, garis batas, koridor Kalimantan, inovasi, MP3EI.